SECURE MOBILE PAYMENT SYSTEM USING NEAR FIELD COMMUNICATION (NFC) TECHNOLOGY - Abdullah Ali Hassan Ghadawi, 1986-, supervisor; Mohd. Shahidan Abdullah, Dr., author; Sekolah Informatiks Termaju (Kuala Lumpur : Universiti Teknologi Malaysia, 2014)
Thesis